# How do you solve 7x - ( x - 3) = 3( x + 10)?

Jun 3, 2018

x=9

#### Explanation:

$7 x - \left(x - 3\right) = 3 \left(x + 10\right)$

First, multiply the brackets
$7 x - \left(x - 3\right) = 3 x + 30$

Calculate the "$7 x$" side
$7 x - x + 3 = 3 x + 30$
$6 x + 3 = 3 x + 30$

Take away the $3$ from both sides
$6 x = 3 x + 27$

Take away the $3 x$ from both sides
$3 x = 27$

Divide both sides by $3$
$x = \frac{27}{3}$
$x = 9$

Jun 3, 2018

$x = 9$

#### Explanation:

$\text{distribute brackets on both sides of the equation}$

$7 x - x + 3 = 3 x + 30$

$6 x + 3 = 3 x + 30$

$\text{subtract "3x" from both sides}$

$6 x - 3 x + 3 = 30$

$3 x + 3 = 30$

$\text{subtract 3 from both sides}$

$3 x = 30 - 3 = 27$

$\text{divide both sides by 3}$

$\Rightarrow x = \frac{27}{3} = 9$

$\textcolor{b l u e}{\text{As a check}}$

Substitute this value into the equation and if both sides are equal then it is the solution.

$\text{left } = 63 - \left(9 - 3\right) = 63 - 6 = 57$

$\text{right } = 3 \left(9 + 10\right) = 3 \times 19 = 57$

$x = 9 \text{ is the solution}$

Aug 10, 2018

$x = 9$

#### Explanation:

We can distribute the parenthesis on the left and right to get

$7 x - x + 3 = 3 x + 30$

Next, let's combine the left side variables to get

$6 x + 3 = 3 x + 30$

Next, let's subtract $3 x$ from both sides to get

$3 x + 3 = 30$

This is unconventional, but since all terms are divisible by $3$, we can divide both sides by $3$ to get

$x + 1 = 10$

Subtracting $1$ from both sides gives us

$x = 9$

Hope this helps!

Aug 10, 2018

$x = 9$

#### Explanation:

$7 x - \left(x - 3\right) = 3 \cdot \left(x + 10\right)$

$6 x + 3 = 3 \cdot \left(x + 10\right)$

$2 x + 1 = x + 10$

$x = 9$